Algorithmic Affective Postmemory and Visual Historical Identity: Madero: The City That Is and Is Not (REVISTA NODO, 2025)
The emergence of generative imagery produced through artificial intelligence (AI) has reinvigorated the possibility of creating impossible images and, specifically, the creation of nonexistent visual memories from an affective dimension. Through the concept of algorithmic postmemory, this study analyzes the project Madero: the city that is and is not by artist Miguel Ángel Camero (2025), situated in Ciudad Madero (Tampico, Mexico), which intersects the autobiographical recreation of family memory with the reimagining of the city's landscape and historical evolution through its houses and buildings. This project serves as a starting point to articulate an emerging conceptual framework that enables reflection on the hybridization of photography with AI and the creation of hypothetical memories, algorithmic indices and punctums, as well as synthetic visual vestiges. This artistic project provides evidence of critical reflection on images and their historical value as memory and identity. It equally traces an emerging horizon regarding the use of AI in generating affective memory images, and engages in a critical debate about historical reading pacts of images, verisimilitude, and the documentary value of visual discourses of believability in the face of a new technological emergence.
Keywords: Algorithmic postmemory; Generative imagery; Artificial intelligence; Visual memory; Identity